2021
DOI: 10.1021/acsmacrolett.1c00617
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Mechanochemical Synthesis of Lactide and 3S-(Isobutyl)morpholine-2,5-dione-Based Random Copolymers Using DBU and Thiourea

Abstract: There is a growing interest surrounding morpholine-2,5-dionebased materials due to their impressive biocompatibility as well as their capacity to break down by hydrolytic and enzymatic pathways. In this study, the ringopening (co)polymerization of leucine-derived 3S-(isobutyl)morpholine-2,5dione (MD) and lactide (LA) was performed via ball-milling using a catalytic system composed of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 3-[3,5bis(trifluoromethyl)phenyl]-1-cyclohexylthiourea (TU). Once the homopolymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…All phenolic-PLA-NPs exhibited a strong, negative ζ-potential value, which is consistent with the presence of lactic acid chain ends and verifies their stability in nature . These findings imply that our approach not only allows for the preparation of phenolic-PLA polymers and nanoparticles in one step but also can be used to obtain phenolic-PLA nanoparticles with a narrow, monomodal size distribution, which is very crucial in a drug delivery synthesis. ,, …”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…All phenolic-PLA-NPs exhibited a strong, negative ζ-potential value, which is consistent with the presence of lactic acid chain ends and verifies their stability in nature . These findings imply that our approach not only allows for the preparation of phenolic-PLA polymers and nanoparticles in one step but also can be used to obtain phenolic-PLA nanoparticles with a narrow, monomodal size distribution, which is very crucial in a drug delivery synthesis. ,, …”
Section: Resultssupporting
confidence: 74%
“…17 These findings imply that our approach not only allows for the preparation of phenolic-PLA polymers and nanoparticles in one step but also can be used to obtain phenolic-PLA nanoparticles with a narrow, monomodal size distribution, which is very crucial in a drug delivery synthesis. 17,29,42 Artificial Neural Network and Sensitivity Assessment Models. The accuracy of the artificial neural network (ANN) has been checked using two new experiments that were not trained in the ANN system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…91,99,181 Recently, Lamaty and Giani expanded the scope to the ROP of morpholine-2,5-dione using ball milling. 182 Initially, the Kim group showed that conventional organic superbase catalysts such as 1,8-diazabicyclo(5.4.0)undec-7-ene (DBU) and triazabicyclodecene can polymerise solid lactide and trimethylene carbonate without a solvent and that ball milling enables efficient initiator-catalyst mixing even at very low concentrations. The number and mass of the milling balls significantly influenced mechanochemical conversion.…”
Section: Chain-growth Polymerisationmentioning
confidence: 99%
“…91,99,181 Recently, Lamaty and Giani expanded the scope to the ROP of morpholine-2,5-dione using ball milling. 182…”
Section: Mechanochemical Synthesis Of Linear Polymersmentioning
confidence: 99%
“…7,8 With the rapid development of organic catalysts in the ROP of cyclic monomers, [9][10][11][12] the organocatalytic ROP of MDs under mild conditions has been achieved recently. [13][14][15][16][17][18] Typical organocatalysts include 1,5,7-triazabicyclo [4.4.0]-dec-5-ene (TBD) and 1,8-diazabicyclo [5.4.0]undecane-7-ene (DBU)/thioureas (TUs). Besides these six-membered MDs, Hocker and Li also synthesized other types of macrocyclic (ester-amide)s by the depolymerization of PEAs and a ring enlargement strategy.…”
Section: Introductionmentioning
confidence: 99%